Amazon and Brazilian Foreign Policy: Analysis of Deforestation Index in the Lula and Bolsonaro Governments (Global Journal of Human-Social Science, 2023)
The international protagonist of the Amazon has gained ground in Brazil's foreign policy, and the rate of deforestation in the region is one of the indicators of this importance. Due to the current focus on the Amazon, the federal government needs to justify the increase in deforestation and present plans to reduce these rates. Realizing the need to better understand the topic, this paper aims to analyze the foreign policy actions developed for the Amazon in the Lula (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) and Bolsonaro (2019-2022) governments, focusing on forest management, considering the beginning of historical monitoring, in 1988, made by the Amazon Deforestation Monitoring Program. In addition, the discussion also contemplates Brazil's performance within the Paris Agreement and the 2030 Agenda. The results of this survey show that the lowest continuous rates of deforestation occurred between 2005 and 2011, while the highest deforestation rates were registered between 2019 to 2021.
Keywords: amazon bolsonaro government lula government foreign policy deforestation